Networking to death: On the dark side of start-ups’ external networking - Ferreira, A. I.; Braun, T.; Carvalho, H.; Abrantes, A. C. M.; Sydow, J. (International Journal of Entrepreneurial Behavior & Research, 2022)
Purpose – Many start-ups do not survive the first few years of business. Previous studies suggest that networks play a role in start-ups’ success, but this positive effect has limits. The purpose of this paper is to answer the call for a better understanding of the dark side of networks and the variables that condition variables’ effect on the likelihood of start-ups’ survival. Design/methodology/approach –Alongitudinal research design includes 139 start-ups (102 from Germany and 37 from Portugal) and a total of 252 participants. A generalized linear mixed model (GLMM)was applied to estimate all the coefficients, to test the mediation (H1), the moderation (H2) and the moderated mediation (H3) while considering the economic situation of the start-up (sales growth), start-ups’ networking behavior, creativity orientation and ultimately the likelihood of survival. Findings – Based on an empirical study from two different countries, the results show that effective networking is contingent on the start-up’s economic situation and creative potential. Specifically, the results point to situations in which early sales growth may lead to external networking, which, in contexts of low creativity-oriented start-ups, can compromise the start-ups’ success. Originality/value – Based on the findings, the authors compare scenarios in which networking increases the chances for start-up survival with situations where networking can have adverse effects. This study highlights the importance of considering specific start-up parameters, such as start-ups’ economic situation and level of creativity orientation, in the business venturing literature.